Factors Related to the Event of Premature Rupture of Membrane in Muna Regency Hospitals - Utami , Wahyu; Tasnim, Tasnim; Akbar Toruntju, Sultan (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction : One of the maternal health programs is to accelerate the decline in numbers. Maternal mortality and maternal mordibity. One ofe the causes of maternal death is infection that can be caused by premature rupture of membranes. Method : This research was quantitative with a cross sectional study design. Study has been carried out in September 2021. The research sample is 164 people obtained by simple random sampling. Processed data using the chi square test. Result : The result showed that the frequency of ANC visit had a phi value of 0,538, parity phi 0,454, anemia phi= 0,438, history of prom phi = 0,720, CPD phi =0,410, trauma in pregnancy phi = 0,573. Conclusion : The conclusion is that there is a relationship between the frequency of ANC visit, Parity, Anemia, History of prom, Cephalopelvik disproportion and trauma during pregnancy with the incidence of premature rupture of membranes in the distric hospital Muna.